Wildlife use of temperate intertidal habitats across tidal and diel gradients - Zoe P. Penno; Amanda E. Bates; Sarah E. Dudas (Estuarine, Coastal and Shelf Science, 2026)

Impact of silica on archaeal isoprenoid hydrocarbons and bacterial n-tricosenes under experimental hydrothermal conditions - L. Weimann; M. Reinhardt; C. Ostertag-Henning; J.-P. Duda; V. Thiel (Organic Geochemistry, 2026)

Cladoceran assemblage changes reveal long-term ecosystem responses to anthropogenically driven seabird declines - Zoe A. Kane; Matthew P. Duda; John P. Smol (Hydrobiologia, 2026)

Laboratory Approach for Characterizing Degraded Shale Material - A. M. Stroisz; M. H. Bhuiyan; N. Agofack; P. R. Cerasi; M. I. Duda (Rock Mechanics and Rock Engineering, 2026)
This research assesses the potential of unpreserved shale core material to provide adequate geophysical characterization, despite its degraded state. Our goal was to reverse degradation processes, focusing on recapturing the in situ saturation state to analyse the fluid's impact on the mechanical and acoustic properties. An extensive testing program was conducted on various sample saturation states, including unconfined compressive strength, scratch, and punch tests, alongside continuous wave and through-transmission methods. For validation, these were paralleled with tests on preserved material of similar properties, that was deliberately degraded to replicate a poor preservation state in a controlled manner. Our findings reveal that even unpreserved or degraded shale cores can yield valuable data, offering insights into in situ properties through simple, low-cost testing methods, which are particularly effective in cases where preparing standard-size testing plugs is unfeasible. However, fully recovering the in situ properties of an unpreserved shale remain a challenge. The results highlight the need for more controlled research to evaluate the chemical and mechanical impacts on unpreserved shales. Developing methods to accurately reverse core damage, caused by inappropriate preservation, and enhance testing reliability require exploring a broader range of shale samples. This research lays the groundwork for refining approaches to restore and understand the true characteristics of shales, moving closer to replicating the in situ state despite existing challenges.

Seabird-mediated changes in sedimentary sterols and stanols - Matthew P. Duda; David C. Eickmeyer; John P. Smol; Jules M. Blais (Quaternary Science Reviews, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Probing growth precursor diffusion lengths by inter-surface diffusion - Stoffel D. Janssens; Francisco S. Forte Neto; David Vázquez-Cortés; Fernando P. Duda; Eliot Fried (Computer Physics Communications, 2025)

Preservation of archaeal core lipids in siliceous hot spring deposits: An experimental study - L. Weimann; M. Reinhardt; C. Ostertag-Henning; J.-P. Duda; V. Thiel (Organic Geochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Hydrocarbons, hydrogen, and organic acids generation by ball milling and batch incubation of sedimentary rocks - A.A. Haluska; E. Blendinger; H. Rügner; D. Buchner; J.-P. Duda; V. Thiel; M. Blumenberg; C. Ostertag-Henning; S. Kümmel; P. Grathwohl (Applied Geochemistry, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Reply to comment on: Carbonaceous matter in ∼3.5 Ga black bedded barite from the Dresser Formation (Pilbara Craton, Western Australia) – Insights into organic cycling on the juvenile earth - L. Weimann; M. Reinhardt; J.-P. Duda; H. Mißbach-Karmrodt; H. Drake; J. Schönig; J. Holburg; L.B. Andreas; J. Reitner; M.J. Whitehouse; V. Thiel (Precambrian Research, 2024)

Carbonaceous matter in ∼ 3.5 Ga black bedded barite from the Dresser Formation (Pilbara Craton, Western Australia) – Insights into organic cycling on the juvenile Earth - L. Weimann; M. Reinhardt; J.-P. Duda; H. Mißbach-Karmrodt; H. Drake; J. Schönig; J. Holburg; L.B. Andreas; J. Reitner; M.J. Whitehouse; V. Thiel (Precambrian Research, 2024)

Aspects of the biological carbon cycle in a ca. 3.42-billion-year-old marine ecosystem - M. Reinhardt; V. Thiel; J.-P. Duda; A. Hofmann; D. Bajnai; W. Goetz; A. Pack; J. Reitner; M. Schanofski; J. Schönig; M.J. Whitehouse; H. Drake (Precambrian Research, 2024)

Environmental optima for common diatoms from Ontario lakes along gradients of lakewater pH, total phosphorus concentration, and depth - Matthew P. Duda; Branaavan Sivarajah; Kathleen M. Rühland; Andrew M. Paterson; Jennifer L. Barrow; Yuanyu Cheng; Elizabeth J. Favot; Kristopher R. Hadley; Roland I. Hall; Kathryn E. Hargan; Clare Nelligan; Euan D. Reavie; et al. (Journal of Paleolimnology, 2023)

Climate oscillations drive millennial‐scale changes in seabird colony size - Matthew P. Duda; Frédéric Cyr; Gregory J. Robertson; Neal Michelutti; Carsten Meyer‐Jacob; April Hedd; William A. Montevecchi; Linda E. Kimpe; Jules M. Blais; John P. Smol (Global Change Biology, 2022)
Seabird population size is intimately linked to the physical, chemical, and biological processes of the oceans. Yet, the overall effects of long‐term changes in ocean dynamics on seabird colonies are difficult to quantify. Here, we used dated lake sediments to reconstruct ~10,000‐years of seabird dynamics in the Northwest Atlantic to determine the influences of Holocene‐scale climatic oscillations on colony size. On Baccalieu Island (Newfoundland and Labrador, Canada)—where the world's largest colony of Leach's storm‐petrel ( Hydrobates leucorhous Vieillot 1818) currently breeds—our data track seabird colony growth in response to warming during the Holocene Thermal Maximum (ca. 9000 to 6000 BP). From ca. 5200 BP to the onset of the Little Ice Age (ca. 550 BP), changes in colony size were correlated to variations in the North Atlantic Oscillation (NAO). By contrasting the seabird trends from Baccalieu Island to millennial‐scale changes of storm‐petrel populations from Grand Colombier Island (an island in the Northwest Atlantic that is subjected a to different ocean climate), we infer that changes in NAO influenced the ocean circulation, which translated into, among many things, changes in pycnocline depth across the Northwest Atlantic basin where the storm‐petrels feed. We hypothesize that the depth of the pycnocline is likely a strong bottom‐up control on surface‐feeding storm‐petrels through its influence on prey accessibility. Since the Little Ice Age (LIA), the effects of ocean dynamics on seabird colony size have been altered by anthropogenic impacts. Subsequently, the colony on Baccalieu Island grew at an unprecedented rate to become the world's largest resulting from favorable conditions linked to climate warming, increased vegetation (thereby nesting habitat), and attraction of recruits from other colonies that are now in decline. We show that although ocean dynamics were an important driver of seabird colony dynamics, its recent influence has been modified by human interference.

Chironomid assemblage changes and chitin degradation in response to ~ 1700-years of seabird population fluctuations at the world’s largest colony of Leach’s Storm-Petrels (Atlantic Canada) - Joeline E. Lim; Matthew P. Duda; John P. Smol (Journal of Paleolimnology, 2021)

Correction to: Categorizing the influences of two large seabird colonies on island freshwater ecosystems in the Northwest Atlantic Ocean - Matthew P. Duda; Neal Michelutti; Xiaowa Wang; John P. Smol (Hydrobiologia, 2021)

Categorizing the influences of two large seabird colonies on island freshwater ecosystems in the Northwest Atlantic Ocean - Matthew P. Duda; Neal Michelutti; Xiaowa Wang; John P. Smol (Hydrobiologia, 2021)

Arctic concentration–discharge relationships for dissolved organic carbon and nitrate vary with landscape and season - Arial J. Shogren; Jay P. Zarnetske; Benjamin W. Abbott; Frances Iannucci; Alexander Medvedeff; Sam Cairns; Megan J. Duda; William B. Bowden (Limnology and Oceanography, 2021)
Climate change is intensifying the Arctic hydrologic cycle, potentially accelerating the release of carbon and nutrients from permafrost landscapes to rivers. However, there are limited riverine flow and solute data of adequate frequency and duration to test how seasonality and catchment landscape characteristics influence production and transport of carbon and nutrients in Arctic river networks. We measured high frequency hydrochemical dynamics at the outlets of three headwater catchments in Arctic Alaska over 3 years. The catchments represent common Arctic landscapes: low‐gradient tundra, low‐gradient and lake‐influenced tundra, and high‐gradient alpine tundra. Using in‐situ spectrophotometers, we measured dissolved organic carbon (DOC) and nitrate (NO 3 − ) concentrations at 15‐min intervals through the flow seasons of 2017, 2018, and 2019. These high‐frequency data allowed us to quantify concentration–discharge (C‐Q) responses during individual storm events across the flow season. Differences in C‐Q responses among catchments indicated strong landscape and seasonal controls on lateral DOC and NO 3 − flux. For the two low‐gradient tundra catchments, we observed consistent DOC enrichment (transport‐limitation) and NO 3 − dilution (source‐limitation) during flow events. Conversely, we found consistent NO 3 − enrichment and DOC dilution in the high‐gradient alpine catchment. Our analysis revealed how high flow events may contribute disproportionately to downstream export in these Arctic streams. Because the duration of the flow season is expected to lengthen and the intensity of Arctic storms are expected to increase, understanding how discharge and solute concentration are coupled is crucial to understanding carbon and nutrient dynamics in rapidly changing permafrost ecosystems.

Long-Term Changes in Terrestrial Vegetation Linked to Shifts in a Colonial Seabird Population - Matthew P. Duda; John R. Glew; Neal Michelutti; Gregory J. Robertson; William A. Montevecchi; Jennifer A. Kissinger; David C. Eickmeyer; Jules M. Blais; John P. Smol (Ecosystems, 2020)

Freshwater diatom assemblages from seabird-inhabited ponds in Hudson Strait, sub-Arctic Canada - Matthew P. Duda; Kathryn E. Hargan; Neal Michelutti; John P. Smol (Polar Biology, 2019)

Breeding eider ducks strongly influence subarctic coastal pond chemistry - Matthew P. Duda; Kathryn E. Hargan; Neal Michelutti; Linda E. Kimpe; Nik Clyde; H. Grant Gilchrist; Mark L. Mallory; Jules M. Blais; John P. Smol (Aquatic Sciences, 2018)

Sound the alarm: A meta‐analysis on the effect of aquatic noise on fish behavior and physiology - Kieran Cox; Lawrence P. Brennan; Travis G. Gerwing; Sarah E. Dudas; Francis Juanes (Global Change Biology, 2018)
The aquatic environment is increasingly bombarded by a wide variety of noise pollutants whose range and intensity are increasing with each passing decade. Yet, little is known about how aquatic noise affects marine communities. To determine the implications that changes to the soundscape may have on fishes, a meta‐analysis was conducted focusing on the ramifications of noise on fish behavior and physiology. Our meta‐analysis identified 42 studies that produced 2,354 data points, which in turn indicated that anthropogenic noise negatively affects fish behavior and physiology. The most predominate responses occurred within foraging ability, predation risk, and reproductive success. Additionally, anthropogenic noise was shown to increase the hearing thresholds and cortisol levels of numerous species while tones, biological, and environmental noise were most likely to affect complex movements and swimming abilities. These findings suggest that the majority of fish species are sensitive to changes in the aquatic soundscape, and depending on the noise source, species responses may have extreme and negative fitness consequences. As such, this global synthesis should serve as a warning of the potentially dire consequences facing marine ecosystems if alterations to aquatic soundscapes continue on their current trajectory.

Erratum to: Emergence of Clostridium difficile infection in tuberculosis patients due to a highly rifampicin-resistant PCR ribotype 046 clone in Poland - P. Obuch-Woszczatyński; G. Dubiel; C. Harmanus; E. Kuijper; U. Duda; D. Wultańska; A. Belkum; H. Pituch (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Emergence of Clostridium difficile infection in tuberculosis patients due to a highly rifampicin-resistant PCR ribotype 046 clone in Poland - P. Obuch-Woszczatyński; G. Dubiel; C. Harmanus; E. Kuijper; U. Duda; D. Wultańska; A. Belkum; H. Pituch (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Immunologically restricted patients exhibit a pronounced inflammation and inadequate response to hypoxia in fracture hematomas - Paula Hoff; T. Gaber; K. Schmidt-Bleek; U. Sentürk; C. L. Tran; K. Blankenstein; S. Lütkecosmann; J. Bredahl; H. J. Schüler; P. Simon; G. Wassilew; F. Unterhauser; et al. (Immunologic Research, 2011)

Involvement of the respiratory chain of gram-negative bacteria in the reduction of tellurite - Stella M. Trutko; Vasilii K. Akimenko; Nataliya E. Suzina; Lyudmila A. Anisimova; Mikhail G. Shlyapnikov; Boris P. Baskunov; Vitalii I. Duda; Aleksandr M. Boronin (Archives of Microbiology, 2000)

Butyltin compounds in sediment and fish from the Polish Coast of the Baltic Sea - Kurunthachalam Senthilkumar; Carolyn A. Duda; Daniel L. Villeneuve; Kurunthachalam Kannan; Jerzy Falandysz; John P. Giesy (Environmental Science and Pollution Research, 1999)

Cardiorespiratory disturbances following antibiotic prophylaxis in general surgery: Reasons for a complex reappraisal of a common problem - B. Stinner; I. Celik, H. Menke, K.-P. Reimund; D. Duda, C. Hasse (Inflammation Research, 1997)